2020
DOI: 10.3390/molecules25194537
|View full text |Cite
|
Sign up to set email alerts
|

Glucosinolates: Natural Occurrence, Biosynthesis, Accessibility, Isolation, Structures, and Biological Activities

Abstract: Glucosinolates (GSLs) are secondary plant metabolites abundantly found in plant order Brassicales. GSLs are constituted by an S-β-d-glucopyrano unit anomerically connected to O-sulfated (Z)-thiohydroximate moiety. The side-chain of the O-sulfate thiohydroximate moiety, which is derived from a different amino acid, contributes to the diversity of natural GSL, with more than 130 structures identified and validated to this day. Both the structural diversity of GSL and their biological implication in plants have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 192 publications
(178 reference statements)
0
77
0
Order By: Relevance
“…SFN triggers cytostasis and apoptosis and also detoxifies xenobiotics [ 7 ]. BITC and PEITC have proved to induce apoptosis in cancer cell lines [ 8 , 9 ]. Nitriles have a weaker chemopreventive effect than ITCs [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SFN triggers cytostasis and apoptosis and also detoxifies xenobiotics [ 7 ]. BITC and PEITC have proved to induce apoptosis in cancer cell lines [ 8 , 9 ]. Nitriles have a weaker chemopreventive effect than ITCs [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the important bioactive compounds are butenyl sulforaphane (SFN), isothiocyanate (BITC) and pentenyl isothiocyanate (PEITC) (Figure 1) [6,7]. The biosynthesis of GSL is one of the more complex processes and more than 130 GSLs have been identified so far [8]. The existence of the different GSL structures is controlled by variability in genes on individual genotypes, especially at loci involved in initial elongation and side-chain modification reactions [9].…”
Section: Introductionmentioning
confidence: 99%
“…Nga [ 16 ] reported that the recovery of glucosinolates from white cabbage in 70% ethanol was around 5.8-fold higher than in water, but it was only 75% of the recovery in methanol. Glucosinolates are usually recovered from plant tissues together with phenolic compounds [ 17 ], then both kinds of molecules have similar behavior in alcohol/water solutions. Do et al [ 18 ] studied the recovery of phenolic compounds from lyophilized L. aromatic in different solvents, reporting recoveries in 75% ethanol and in 75% methanol of around 5-fold higher than recovery in pure water.…”
Section: Discussionmentioning
confidence: 99%
“…Accelerated solvent extraction (ASE) is a technique carried out under high pressure and an inert atmosphere with a range of extraction temperatures from 35 to 200°C. This intensification method has been applied to recover secondary metabolites from Brassica biomass (Mohn et al, 2007;Blažević et al, 2020;Nguyen et al, 2020), including SinA and its derivatives (Li and Guo, 2016;Nandasiri et al, 2019). Aqueous alcoholic extraction of phenolics at high temperature (140-180°C) and high pressure resulted in better extraction yield than conventional method (Nandasiri et al, 2019).…”
Section: Intensified Recovery Of Sinapic Acid and Derivatives Using Physical Acceleratorsmentioning
confidence: 99%